Goal configuration in a global industry context - Roth, Kendall; Ricks, David A. (Strategic Management Journal, 1994)
Abstract This study analyzes the goal configuration of 126 firms, based in Japan, U.K. and U.S., competing in global industries. The results indicate that firm nationality and internationalization do not affect the firm's goal configuration. The breadth of the firm's reward system was found to be related positively to a dispersed goal configuration and, within global and multifocal industry segments, a congruence between goal configuration and industry position was found to be associated positively with performance.